A Utilitarian Perspective of Social and Medical Contributions to Three Illustrative Conditions, and Recent UK NHS Policy Initiatives - Middleton, Hugh; Shaw, Ian (Taylor & Francis, 2007)
Background: To date debate concerning the relative merits of social and medical sciences has been largely academic. Aims: To outline and critically appraise a utilitarian approach to mental health research that reflects a critical realist perspective. Method: Consideration of the relative utility of differing approaches to illustrative ‘‘psychiatric’’ disorders, and recent policy initiatives. Results: Socially relevant outcomes of Bipolar Affective Disorder are determined by influences that operate independently of the characteristic instability of mood. There is now a highly specific and effective psychological treatment for Panic Disorder. Its benefits are still not fully exploited because of continuing lay and professional focus upon the condition’s social manifestations. Great numbers of people presenting in primary care are unhelpfully caused to adopt the role of ‘‘patient’’ due to practices limiting the professional response to a medical one. Such practices reflect public and professional perceptions of the nature of ‘‘mental health difficulties’’ much more than they do the achievements of medicine. Recent policy-supporting initiatives influencing UK NHS mental health services are much more likely to be supported by social sciences than by medical research. Conclusions: There is considerable scope for a contribution to applied mental health research from frameworks and methodologies that are rooted in a social sciences perspective.